Effect of the blending and diffusion processes between aged and virgin asphalt on the low-temperature crack resistance of plant hot-mix recycled asphalt mixtures - Tao, Wensheng; Yao, Yuquan; Yang, Shunxin (Frontiers in Materials, 2025)
The blending and diffusion behaviors between aged and virgin asphalt significantly affect the performance of recycled asphalt mixtures. To investigate the influence of mixing process parameters and post-production time–temperature coupling on the blending and diffusion characteristics, as well as their impact on the low-temperature crack resistance of recycled asphalt mixtures, this study designed an AC-20 recycled asphalt mixture with 40% reclaimed asphalt pavement (RAP), and constructed an evaluation model to quantify the blending degree. A single-factor controlled variable method was employed to investigate the evolution of blending and diffusion characteristics under different conditions, and the low-temperature crack resistance of the mixtures was evaluated using the semicircular bending test (SCB). Furthermore, the relationship between the blending and diffusion characteristics and the low-temperature crack resistance under different influencing factors was analyzed. The results indicate that variations in RAP preheating temperature, mixing time, and mixing temperature can influence both the blending degree between aged and virgin asphalt and the low-temperature fracture energy, generally showing a positive correlation, except in the case of RAP preheating temperature. Under the post-production stage time–temperature coupling condition, further diffusion occurs between aged and virgin asphalt, resulting in a more uniform blended asphalt interface. Although longer conditioning improves diffusion uniformity, it may also induce aging of the blended asphalt, leading to a trend in which the low-temperature performance initially improves and then declines. Considering the balance among blending degree, diffusion uniformity, and low-temperature crack resistance, it is recommended that the RAP preheating temperature be maintained at approximately 110 °C and not exceed 130 °C; The mixing time and mixing temperature of recycled asphalt mixtures in the laboratory should be no less than 150 s and 160 °C, respectively. Additionally, the interval between production and final paving should be controlled within 90–180 min to ensure adequate performance.